The effect of nebivolol on erectile function in the cases with coronary artery bypass surgery: A protocol for a systematic review and meta-analysis of randomized controlled trials - Yang, Yali (Medicine (Baltimore), 2020)
BACKGROUND: Erectile dysfunction is a common disease. It affects the quality of life of both husband and wife and its prevalence is higher in patients with overt cardiovascular disease or cardiovascular risk factors. In recent years, multiple studies confirm that nebivolol exerts protective effects on erectile function against the disruptive effects of cardiopulmonary bypass in patients undergoing coronary artery bypass grafting, but its quality and efficacy have not been systematically evaluated. Therefore, it is necessary to carry out a systematic review and meta-analysis to fully evaluate the efficacy and safety of nebivolol on erectile function in the cases with coronary artery bypass grafting. METHODS AND ANALYSIS: Chinese and English literature of nebivolol on erectile function in the cases with coronary artery bypass surgery published before August 31, 2020 will be comprehensive searched in PubMed, Cochrane Library, EMBASE, WANFANG, China National Knowledge Infrastructure, VIP Chinese Science and Technology Journal Database, Chinese biomedical document service system, and Clinicaltrials.gov. Only randomized controlled trials that meet the eligibility criteria will be included. Two researchers will independently complete literature screening, data extraction and assess the risk of bias, and the third investigator will handle disagreements. Our main evaluation includes 2 outcome indicators including the international index of erectile function 5 score and adverse events. RevMan 5.3 and Stata 14.0 will be used to conduct this systematic review. The preferred reporting items for systematic reviews and meta-analysis protocols (PRISMA-P) statement is followed in this protocol and the PRISMA statement will be followed in the completed systematic review. CONCLUSION AND DISSEMINATION: The efficacy and safety of nebivolol on erectile function in the cases with coronary artery bypass grafting will be evaluated. We will publish the results of this systematic review in peer-reviewed journals to provide new evidence to clinicians. ETHICS AND DISSEMINATION: Ethical approval is not required as the review is a secondary study based on published literature. The results will be published in a public issue journal to provide evidence-based medical evidence for urologists and andrologists to make better clinical decisions. REGISTRATION INFORMATION: INPLASY202060110.